124k views
4 votes
Evaluate each expression.

6! =



3! • 2! =



StartFraction 6 factorial Over 3 factorial EndFraction =

2 Answers

7 votes

Answer:

720

12

120

Explanation:

User Tom Kris
by
4.6k points
2 votes

Answer:

720

12

120

Explanation:

Factorials

We must recall that the factorial of a number n (positive or zero) is the product of all the integers from n down to 1


n!= n(n-1)(n-2)...1

Let's evaluate the given expressions


6!=6\cdot 5\cdot 4\cdot 3\cdot 2\cdot 1=720

Similarly


3!\cdot 2!=(3\cdot 2\cdot 1)\cdot (2\cdot 1)=6\cdot 2=12

Finally


\displaystyle (6!)/(3!)=(6\cdot 5\cdot 4\cdot 3\cdot 2\cdot 1)/(3\cdot 2\cdot 1)


\displaystyle (6!)/(3!)= (720)/(6)=120

User Bonhoffer
by
4.7k points